The First Endoscopic Sleeve Gastroplasty and Transoral Outlet Reduction in Thailand: Case Report and Literature Review - Taweerutchana, Voraboot; Maipang, Kotchakon; Srisuworanan, Nicha; Tovikkai, Parichat; Jirapinyo, Pichamol; Thompson, Christopher C.; Pausawasdi, Nonthalee (Siriraj Medical Journal, 2021)
Obesity is becoming a universal healthcare problem. The role of endoscopic bariatric and metabolic therapies is emerging in the management of obesity and its related conditions. The endoscopic treatment can be used as a primary weight loss procedure and a revision procedure after bariatric surgery. While the prevalence of obesity has been rising over the past two decades in Thailand, the treatment options have been limited to diet and exercise, pharmacological treatment, and bariatric surgery until recently. In 2020, an endoscopic full-thickness suturing device was introduced to Thailand, leading to successful endoscopic bariatric therapy using a suturing device in Thai patients. This article intends to report the first successful endoscopic sleeve gastroplasty and transoral outlet reduction in Thailand with a mini-review focusing on these two procedures’ outcomes.